Religious Education for Children in the Family Environment of PAIS Teacher Teaching Fullday School at MAN 2 Banjarmasin City - Rusdiah, Rusdiah; Manaf, Abdul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study discusses religious education in the family environment of PAIS teachers who teach at MAN 2 Model Kota Banjarmasin with a full-day school system, covering four main aspects: five daily prayers, fasting, reading the Qur'an, and faith and morals. This type of research is field research with a qualitative descriptive approach, where data is collected through observation, interviews, and documentation. The subjects of the study were PAIS teachers teaching full-day school with children aged 6–12 years, and the object of the study was religious education in their family environment and the factors that support and inhibit it. Data were analyzed using a qualitative descriptive method, and conclusions were drawn through an inductive approach. The results showed that supporting factors for religious education include adequate parental educational background, availability of time, a conducive environment, and the availability of learning facilities and infrastructure at home. However, limited time and a less supportive environment are the main obstacles in its implementation.